Pengaruh Komposisi Media Tanam (Perbandingan Tanah, Pupuk Kandang, dan Arang Sekam) Terhadap Pertumbuhan dan Hasil Tanaman Kangkung Darat (Ipomoea reptans Poir) - Shirly S. Oematan; Yosefina R. Y. Gandut; Antonius S. S. Ndiwa; C. F. F. Higa Huki (Wana Lestari, 2022)
This research was carried out in the experimental garden of the UPT Integrated Field Laboratory / Center for Excellence in Science and Technology on Dry Land Islands, Nusa Cendana University, which was carried out from March to May 2022. growth and yield of land kale and knowing the composition of the growing media (soil ratio, manure and husk charcoal) that can provide the best growth and yield of land kale. This study is an experimental experiment designed using a completely randomized design (CRD) with 7 treatments and 5 replications. The treatments tested in the form of planting media composition (Comparison of Soil, Manure, Husk Charcoal), were as follows: (T0) = 100% soil; (T1) = Soil 1: Manure 1; (T2) = Soil 1 : husk charcoal 1; (T3) = Soil 1: Cow manure 1: Husk charcoal 1; (T4) = Soil 2: Manure 1; (T5) = Soil 2: Husk Charcoal 1 and (T6) = Soil 2: Manure 1: Husk Charcoal 1. The results showed that the combination of planting media (comparison of soil, manure, and husk charcoal) had a significant effect on plant height, number of leaves, gross fresh weight, and net fresh weight of kale as well as the combination treatment of soil and manure (1 : 1) gave the best results for plant height, number of leaves, fresh weight, net weight, which were 18.74 cm for height, respectively. plants, 8.44 leaves for the number of leaves, 17.67 grams for fresh weight and 12.84 grams for plant net weight.